2003
DOI: 10.1093/gerona/58.7.m631
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Difference in Hip Joint Position Sense Between Young and Older Groups?

Abstract: In this study, no difference in hip JPS was found between young and older subjects. Accuracy was greater in the inner range, with active repositioning demonstrating higher precision compared to passive repositioning of the limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 15 publications
6
38
0
Order By: Relevance
“…This absence of significant age-related difference supported previous studies showing that older adults were able to reach levels of proprioceptive control performance comparable to those observed in young adults (Batavia et al 1999;Boisgontier et al 2012;Deshpande et al 2003;Goble et al 2012a, b;Marks 1996;Pickard et al 2003). The splitting of the total error into variable and constant errors confirmed this similar pattern of end-point results between age groups.…”
Section: End-point Performancessupporting
confidence: 88%
See 1 more Smart Citation
“…This absence of significant age-related difference supported previous studies showing that older adults were able to reach levels of proprioceptive control performance comparable to those observed in young adults (Batavia et al 1999;Boisgontier et al 2012;Deshpande et al 2003;Goble et al 2012a, b;Marks 1996;Pickard et al 2003). The splitting of the total error into variable and constant errors confirmed this similar pattern of end-point results between age groups.…”
Section: End-point Performancessupporting
confidence: 88%
“…It was hypothesised that (1) the ability to accurately match the proprioceptive target in the self-selected speed condition was not different between young and older adults. Indeed, although it was against an increased cognitive cost and additional neural resources, previous studies showed that older adults were able to reach levels of proprioceptive control of movement comparable to those of young adults (Batavia et al 1999;Boisgontier et al 2012;Deshpande et al 2003;Goble et al 2012a, b;Heuninckx et al 2008;Marks 1996;Pickard et al 2003). However, on the basis of the differences observed in motor imagery (Personnier et al 2010(Personnier et al , 2008Skoura et al 2005) and kinematic studies (Elliott and Hansen 2010;Goggin and Meeuwsen 1992;ReyRobert et al 2012; Seidler-Dobrin and Stelmach 1998), we hypothesised that (2) older adults were not able to reach the same level of end-point performance as the young adults in the fast speed condition due to the temporal constraints, making it impossible to use additional sub-movements to compensate for the presumably altered internal models.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that Pickard et al [52] did not find significant differences when comparing the hip joint position between sedentary young subjects and active aged subjects (mean age: 75±6 years), that practiced physical activity 10 (range 3 to 20) hours per week. The authors justified the lack of differences between subjects because the aged group was physically active.…”
Section: Mechanisms Of Proprioception Deterioration With Agingmentioning
confidence: 91%
“…Sense of limb movement determines detection of passive motion of the limb [25]. Both components of proprioception are important for the generation of smooth and coordinated movements, maintenance of normal body posture, regulation of balance and postural control, and motor learning and relearning [52,73]. This importance was demonstrated by Ghez and Sainburg [21] and Ghez et al [22] using deafferented patients.…”
Section: Introductionmentioning
confidence: 96%
“…The limitation was not addressed as it is extremely difficult to accurately quantify one's lifelong history of physical activity. As a result, dividing participants based on the results of a physical activity questionnaire remains a common practice in motor control research (e.g., Adamo et al 2007;Adamo et al 2009;McGregor et al 2011;Petrella et al 1997;Pickard et al 2003;Wright et al 2011).…”
Section: Classification Of Physical Activity Level As a Study Limitationmentioning
confidence: 99%